OP88 Evaluating the move to, and implementation in 2018 of, smoke-free prison policy in scotland: the tobacco in prisons study (TIPS). (3rd September 2019) - Hunt, K; Brown, A; Semple, S; Eadie, D; Sweeting, H; Demou, E; Leyland, A; Craig, P; Dobson, R; Bauld, L
Abstract : Background: Until recently, prisons had partial exemption from UK policies which banned smoking in most enclosed public spaces and were one of few UK workplaces in which staff were exposed to secondhand smoke (SHS) and in which smoking remained normative. In 2016 the Tobacco in Prisons (TIPs) study documented high SHS concentrations in prison residential and other areas, informing new policy, implemented in November 2018, to prohibit smoking throughout all Scottish prisons. Although smoking bans have been introduced in prison systems elsewhere (e.g. England, New Zealand, parts of Australia and the USA), TIPs forms the most comprehensive study internationally of the process and impact of introducing smokefree prisons. Methods: This three-Phase study utilised mixed methods including: 1) surveys with staff and prisoners, focus groups and interviews with prison and NHS staff, and qualitative interviews with prisoners - to assess health, smoking status, beliefs about smoking, e-cigarettes, smoking cessation provision, and the perceived desirability, benefits and challenges of smokefree prison policy; 2) objective measures of SHS before, during and 6 months after smokefree policy was implemented; and 3) use of routinely collected data (e.g. sickness absence, prisoner 'canteen' purchases and medication use) to assess impact of the policy. Results: Phase 1 surveys with prisoners confirmed very high levels of prisoner smoking pre-ban (72%). Phase 1 and 2 survey and interview data demonstrated that prisoners were less in favour of smokefree policies than staff, but supported the introduction of e-cigarettes in the move to smokefree prisons. Survey and interview data from staff and prisoners indicated concerns about the challenges of introducing smokefree policy. Phase 2–3 data showed air quality improved in all prisons comparing Phase 1 (2016) data with the first full working day (3rd December 2018) post-implementation (overall median reduction -81% inter-quartile range -76 to -91%). Post-implementation indoor PM2.5 concentrations suggested minimal smoking activity during the period of measurement. Immediately prior to the introduction of smokefree policy, prisoners and staff largely reacted favourably to the introduction of e-cigarettes, whilst still voicing some reservations about their use and safety. Discussion: This is the first comprehensive evaluation of changes in SHS concentrations, and the attitudes, perceptions, health and behaviours of people living and working across all prisons within a country that has introduced nationwide prohibition of smoking in prisons. Early Phase 3 results suggest that a smoke-free prison policy reduces the exposure of prison staff and prisoners to SHS and can be implemented despite considerable challenges.